Features of the formation of specific immunity after vaccination against viral hepatitis B in children and young people - E. O. Kochetova; O. V. Shamsheva; I. V. Polesko; A. V. Semenenko; O. A. Maiorova; V. V. Belyakova; V. V. Gorev (Лечащий Врач)
According to the World Health Organization, there are about 300 million people worldwide living with chronic hepatitis B, with about 1.5 million new infections occurring each year. In the Russian Federation, starting from the new century, there has been a gradual decrease in the incidence of acute hepatitis B, which retains the status of a socially significant viral infection. Vaccination against hepatitis B was included in the National Immunization Schedule in December 1997. by order of the Ministry of Health of the Russian Federation No. 375, which was later (in September 1998) enshrined in the Federal Law "On Immunoprophylaxis of Infectious Diseases". Currently, the main indicator of the body's protection against infection with the hepatitis B virus after immunoprophylaxis is the level of post-vaccination antibodies of the IgG class to HBsAg (anti-HBs), which can be determined using serological tests. The results of a study of the intensity of post-vaccination immunity against hepatitis B in children and young people vaccinated in the first year of life with a monocomponent recombinant hepatitis B vaccine are presented. A high proportion of children (85.5%) with anti-hepatitis B indicators at low (10-100 mMU/ml) or practically undetectable (below 10 mMU/ml) has been established.ml) levels. The results obtained correlate with a high proportion of children with a burdened premorbid background (87.1%) and, probably, the presence of immunodeficiency conditions. In young people, the proportion of seronegativation was 43.2%, and in combination with persons with low-level antibodies - 82.8% of the total number of examined. Thus, due to the weak response to the recombinant hepatitis B vaccine and the high medical and social significance of hepatitis B infection, various approaches are currently being developed to enhance the effectiveness of vaccination: changes in the vaccination regimen; correction of immune system functions to restore an adequate response to vaccine preparations, the use of various adjuvants, including recombinant interferons.